9-8x-7-4x=5

Simple and best practice solution for 9-8x-7-4x=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-8x-7-4x=5 equation:


Simplifying
9 + -8x + -7 + -4x = 5

Reorder the terms:
9 + -7 + -8x + -4x = 5

Combine like terms: 9 + -7 = 2
2 + -8x + -4x = 5

Combine like terms: -8x + -4x = -12x
2 + -12x = 5

Solving
2 + -12x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -12x = 5 + -2

Combine like terms: 2 + -2 = 0
0 + -12x = 5 + -2
-12x = 5 + -2

Combine like terms: 5 + -2 = 3
-12x = 3

Divide each side by '-12'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| 5(4x+9)-6x=8x+12 | | 253+c=-24 | | 16j-4= | | (4x-2)(3x-4)=9 | | (-a-7b+6)7ab= | | .31=log(x) | | 7+x-3x=29 | | 34-3x=9-8x | | 8(y-2)+8=3(y-4)-2 | | 4x-3(7-x)=7 | | (2xy^2+2y)dx+(2x^2y+2x)dy=0 | | 3x-72-2x=35 | | h=-t^2+2t | | x-429.30=120.44 | | 17.6n-17.28=21.8n-41.8 | | -[3x-(2x+2)]=-5-[3(2x-4)-3x] | | ln(x+4)-ln(x-2)=2 | | 3x+30+27y=0 | | -6(w+1)-w-12=-7(w+4)+10 | | -3(a+8)=a+2(5a-7) | | 20+5x=150 | | 4m+45=61+2m | | I=Crt | | 4-5x=39 | | 4s+20=200 | | -10p-5(4-4p)=6(p-2)-16 | | 5p+7p=72 | | 7+8=28+x | | 0.39=log(x) | | 6x-4=14x-42 | | 48-9x=-27+6 | | 6x-4=14-42 |

Equations solver categories